Parliamentary Activity, Re-Selection and the Personal Vote. Evidence from Flexible-List Systems. Issue 4 (31st January 2018) - Däubler, Thomas; Christensen, Love; Linek, Lukáš
Abstract: In this article, we analyse how the degree of parliamentary activity affects both individual MPs' performance in the candidate selection process within the party and their popularity with voters at the electoral stage. We expect that parliamentary work of MPs matters less for voters' evaluations of MPs because of limited monitoring capacities and lower salience attached to this type of representation. The empirical analysis uses data from recent elections in the Czech Republic and Sweden. During the analysed period, these countries further personalised their flexible list electoral systems. Our results suggest that parties hold MPs accountable mainly through the threat of non-re-selection rather than by assigning them to a promising list position. While there is no evidence that voters consistently reward MPs' effort, the case of the Czech elections in 2010 shows that they may do so if context draws attention to individual MPs' work.